Socialization of Law Number 32 of 2009 Concerning Environmental Protection and Management in Gadingan Village, Mojolaban District, Sukoharjo Regency - Triwanto, Triwanto; Rahayu, Alya Maya Khonsa; Riyadi, Achmad; Prabowo, Rizaldi Setyo (AIWADTHU: Jurnal Pengabdian Hukum, 2025)
Introduction: This study aims to determine how the socialization of Law Number 32 of 2009 concerning Environmental Protection and Management in Gadingan Village, Mojolaban District, Sukoharjo Regency, and to evaluate public understanding of the contents and implementation of the law.Purposes of The Devotion: Socialization regarding environmental protection and management is very important to increase public awareness in maintaining environmental sustainability and fulfilling legal obligations related to sustainable natural resource management. Method of The Devotion: Legal counseling activities in Gadingan village, Mojolaban District, Sukoharjo Regency were carried out by the Panel Discussion method where the presenter delivered the material in turn, then continued with a question and answer between the speaker and the community.Results Main Findings of the Devotion: The results of the study indicate that the socialization carried out by the local government is still limited, both in terms of frequency and reach of participants. The community in Gadingan Village still has a low understanding of the importance of environmental protection based on the law. Therefore, it is necessary to increase the intensity of socialization and more active community involvement in environmental programs. This study is expected to contribute to efforts to increase community understanding of the importance of environmental management and protection in accordance with the provisions in force in Law Number 32 of 2009.